(untitled) (Педагогіка вищої та середньої школи, 2006)
The aims of the lessons in the Ukrainian language, which are enlarging and activization of lexicon, forming and developing of the skills o f oral and written spuch, supplying of the mental development of pupils, are defined on the present stouge of the new junior school’s development. The most important device of influence on a child is beauty and magnificence, power and expressiveness of native words. Children can understand the dupest colour of words through the words the beauty enters their souls.